Exploring the linkage between root system architecture and grain iron content in wheat (Triticum aestivum L.) - Sultana, Rashida; Kiran, Aysha; Sanaullah, Muhammad; Wakeel, Abdul (Frontiers in Sustainable Food Systems, 2023)
Iron (Fe) is a vital element that is equally important for plants, animals, and humans. High Fe concentrations in wheat grains have reliance on plant roots, the hidden half of the plant with a role in nutrient mining. Enhanced grain Fe content of wheat can positively mitigate Fe malnutrition in poor populations. In the present study, 100 wheat varieties were studied to identify the root architectural characteristics in relation to grain Fe concentration. Germinated seeds were transplanted in a rhizobox kept in a standard nutrient solution and were harvested 12 days after transplanting. Roots were scanned and the images were processed using smart root software. A total of 12 wheat varieties, which had a vigorous and weak root system architecture (RSA), in combination with higher and lower Fe grain concentrations, were selected using principal component analysis. The uptake and translocation of Fe from root to shoot were determined through a pot experiment conducted for the above-mentioned 12 wheat varieties, with or without Fe fertilizer applied as FeSO4 to the soil. The data obtained from the pot experiment revealed that Dharabi-11 with vigorous RSA exhibited the highest grain Fe concentration (57.20 mg kg−1), low phytate concentration (6.50 mg kg−1), and maximum 1,000 grain weight, whereas Ujala-16 with weaker RSA had the lowest grain Fe concentration (13.33 mg kg−1), highest phytate concentration (9.07 mg kg−1), and lowest 1,000 grain weight. There were also varieties showing higher grain Fe concentrations with weaker RSA and vice versa. Although it is indicated that vigorous RSA leads to high grain Fe concentration, it is not the sole factor in high grain Fe concentration. Nevertheless, the results demonstrate that large genetic diversity is available among indigenous wheat germplasm in terms of grain Fe concentration and RSA. This information may be utilized in the development of new varieties through conventional and marker-assisted breeding programs using RSA traits for Fe biofortification in wheat, leading to the mitigation of Fe malnutrition.